Neonatal Compartment Syndrome as a Result of Thromboembolic Event. Issue 11 (November 2019) - Zajac, Jocelyn C.; Mantilla-Rivas, Esperanza; Tilt, Alexandra; Bryant, Justin R.; Oh, Albert K.; Rogers, Gary F.
Abstract : Summary: Neonatal compartment syndrome is a rare condition characterized by progressive limb ischemia and tissue necrosis manifesting at birth or in the immediate postpartum period. Early recognition of clinical features and immediate surgical intervention offer the best prognosis, but unfamiliarity with this uncommon entity often results in delayed diagnosis and catastrophic consequences, including limb amputation. We present a case in a preterm neonate who developed a proximal arterial thrombus after sustaining limb ischemia in utero. This case demonstrated that even delayed treatment with appropriate therapy can result in salvage of the limb. Clinicians should be aware of the characteristic skin findings and institute appropriate measures to determine the presence or absence of compartment syndrome.